Rheological behaviour of thermotropic and lyotropic liquid crystalline phases of Guerbet branched chain glycolipids - Mislan, Azwa Amanina; Foong, J.L. Nigel; Saharin, Siti Munirah; Zahid, Noor Idayu Mat (Elsevier, 2019)
Glycolipids, being low toxicity, biodegradable and showing surface activity, are a candidate for an alternative surfactant known as biosurfactant. In this study, two Guerbet branched chain glycolipids namely 2-hexyl-decyl-β-D-glucoside (β-Glc-C10C6) and 2-hexyl-decyl-β-D-maltoside (β-Mal-C10C6) were prepared and their mesomorphic behaviours in dry and hydrated conditions were characterized and compared using rheology. These glycolipids possessed the same number of carbons in their alkyl chain but differed in headgroup size. β-Glc-C10C6 exhibited inverse hexagonal phase (H2) in thermotropic but formed inverse bicontinuous cubic phase (V2) of space group Ia3d and Pn3m upon contact with water at different concentration ranges. The self-assembly of β-Mal-C10C6 was dominated by the lamellar phase (Lα) in both conditions. A shear viscosity test indicated that all mesophases formed by these Guerbet glycolipids exhibited shear thinning behaviour. Oscillation measurements were obtained within the linear viscoelastic regime. In general, the viscoelastic studies on the thermotropic H2 (β-Glc-C10C6) and Lα (β-Mal-C10C6) phases showed that the storage modulus (G′) and loss modulus (G″) increased with the frequency, indicating the typical viscoelastic response for non-Newtonian fluid at the selected temperatures. The lyotropic inverse bicontinuous cubic of β-Glc-C10C6 containing different water concentrations showed the dominance of G’ over G” at the range of frequencies and temperatures tested. A similar finding was observed for the lyotropic Lα phase of β-Mal-C10C6 but with a lower magnitude of structural strength. © 2019 Elsevier B.V.